The Use of Facilities of Positive Cross-Cultural Psychotherapy as Interactive Technologies of Teaching in Preparation of Specialists of Preschool Education - Dvizhona, Oksana (Pedagogical Discourse, 2012)
The author of the article offers the technique of combination of different psychotherapy directions, positive cross-cultural psychotherapy, art-therapy, and psychodrama for conducting practical lessons on practical work in psychology and pedagogics in preparation of specialists of preschool education.